Silver decorated CeO2 nanoparticles for rapid photocatalytic degradation of textile rose bengal dye - G. Murugadoss (Nature Portfolio, 2021)
Abstract High quality silver (Ag) decorated CeO2 nanoparticles were prepared by a facile one-step chemical method. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), High resolution transmission electron microscopy (HR-TEM), fourier transform infrared spectrometer (FT-IR), electron paramagnetic resonance (EPR), X-ray photoelectron spectroscopy (XPS), UV–Visible absorption (UV–Vis), photoluminescence (PL) and thermogravimetric analysis. The decoration of Ag on CeO2 surface was confirmed by XRD, EPR and HR-TEM analysis. Harmful textile pollutant Rose Bengal dye was degraded under sunlight using the novel Ag decorated CeO2 catalyst. It was found that great enhancement of the degradation efficiency for Ag/CeO2 compared to pure CeO2, it can be ascribed mainly due to decrease in its band gap and charge carrier recombination rate. The Ag/CeO2 sample exhibited an efficient photocatalytic characteristic for degrading RB under visible light irradiation with a high degradation rate of 96% after 3 h. With the help of various characterizations, a possible degradation mechanism has been proposed which shows the effect of generation of oxygen vacancies owing to the decoration of Ag on the CeO2 surface.